Розсіяння світла на шорсткій поверхні кварцу з профілем у вигляді трикутних виступів, які періодично повторюються - Grigoruk, V. I.; Kanevskii, V. I.; Kolenov, S. A.; Sidorenko, V. S. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2017)
Calculation of evanescent field in near-zone of quartz rough surface is presented. 2D vector Helmholtz equation by means of finite element approach is used. Shape of quartz surface is chosen as sequence of surface three-cornered form irregularities. It shown that (a) contrast range of evanescent field practically does not depend on length of scattering wave at illumination of quartz rough surface on condition of total light reflection especially in the case of height of irregularities ()is insignificant (£1nm); (b) the reflection light coefficient does not depend on the parameter; (c) the contrast of quartz rough surface diminishes when its correlation length increases; (d) on the average, distribution of evanescent field along the surface of quartz repeats the form of the rough surface.